Nye aktører på det danske bogmarked - Litteratursociologiens udfordringer - Worsøe-Schmidt, Lisbeth (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
Traditionelly, since Robert Escarpit (1958), sociology of literature has analysed the book world as a book communications circuit. Typically, these models function as flow charts showing the transformation of a manuscript to a book within a print culture. The question is, however, if this approach is still suitable for analysing and understanding current changes within the book world. The aim of this article is to step behind the institutional flow charts by examining two distinct phenomena emerged as result of digitization and liberalisation of the Danish book market, NewPub and Mofibo, by means of Johan Svedjedal’s analysis of functions in combination with core concepts in Raymond Williams’ cultural theory. In addition, the concepts of mediation and mediatization are discussed. The main conclusions are that the circuit model reproduces the dominant culture and its omissions, especially communication, while analysis of functions coupled with Williams’ concepts is well suited for analysing changes within the book world and, in addition, qualifies the difference between mediation and mediatization. Mofibo may be seen as a new institution within the dominant culture, while NewPub rather is an alternative, emergent formation.